Challenges in the Halal Industry Ecosystem: Analyzing the Halal Certification Process for Micro, Small, and Medium Enterprises in Lombok, West Nusa Tenggara - Prawiro, Atmo; Fathudin, Fathudin (Mazahib, 2023)
This article examines the challanges of the halal industrial ecosystem by studying halal certification for MSME (Micro, Small, and Medium Enterprises) in Lombok. Halal certification has a good impact on small and medium businesses in Indonesia. Although previous research indicates that the proportion of halal-certified micro, small, and medium enterprises (MSMEs) in Lombok is still under 20%, this figure is steadily increasing, allowing for open competition. This article employs a qualitative methodology with a socio-legal economic analysis approach. Data were gathered through interviews with MSME business owners, Muslim consumers, and halal policy makers in Lombok. The findings reveal that halal certification plays a crucial role in enhancing MSME operations and promoting the development of halal tourism in Lombok. However, the complexity of halal certification requirements and the obstacles MSME faces in Lombok must be ruled out effectively. By increasing knowledge, understanding, and awareness of MSME actors regarding halal certification rules and improving administrative processes related to halal certification, MSME in Lombok will better utilize the market potential for halal products. Keywords: Halal industry, halal certification, MSME, impact of certification